2000
DOI: 10.1097/00002030-200004140-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of genotypic resistance to nucleoside analogues and protease inhibitors in Spain

Abstract: The prevalence of primary genotypic resistance to NRTI and PI in Spain was 17% and 6%, respectively. Zidovudine, lamivudine, indinavir and ritonavir were the drugs most frequently affected. These data support the use of resistance testing prior to the introduction of first-line antiretroviral therapies in Spain. Among pre-treated subjects, drug resistance genotypes were less prevalent in those who began HAART as initial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 17 publications
4
11
1
Order By: Relevance
“…Nearly 80% of samples from treatment-experienced patients showed resistant genotypes at the pol gene, a rate similar to that reported in previous studies conducted with subjects whose antiretroviral treatment failed (6,7,15 Extensive polymorphisms were observed in the gag region throughout the p7, p1, and p6 proteins. However only four point mutations localized immediately upstream of the pol gene, in the cleavage sites, were more frequently found among treatment-experienced subjects ( Table 1).…”
supporting
confidence: 86%
“…Nearly 80% of samples from treatment-experienced patients showed resistant genotypes at the pol gene, a rate similar to that reported in previous studies conducted with subjects whose antiretroviral treatment failed (6,7,15 Extensive polymorphisms were observed in the gag region throughout the p7, p1, and p6 proteins. However only four point mutations localized immediately upstream of the pol gene, in the cleavage sites, were more frequently found among treatment-experienced subjects ( Table 1).…”
supporting
confidence: 86%
“…However, in clinical practice, virologic failure of protease inhibitor-containing therapy occurs in a significant fraction of the treated population (19,22,42,46,52,70). Virologic failure of protease inhibitor treatment is often due to the selection of HIV-1 strains with mutations in the pro gene, which encodes the viral protease (PR), and in specific protease cleavage sites encoded in the gag gene that collectively confer reduced drug susceptibility to the harboring strain (11,12,28,36,43,47,72).…”
mentioning
confidence: 99%
“…Cross-sectional drug resistance surveys have been performed in Spain over the last four years (4,5,11,12). The results of these studies have shown that the rate of genotypic resistance is above 70% for nucleoside analogues (NA) and 27% for protease inhibitors (PI) for subjects previously exposed to antiretroviral drugs.…”
mentioning
confidence: 99%